Low-dose statins combined with repetitive transcranial magnetic stimulation reduce post-stroke depression - Cui, Chaohua; Cai, Chuhua; Yin, Qiulian; Guan, Haoye; Long, Tonghua (Frontiers in Neurology, 2025)
BackgroundThe effectiveness of statins in preventing post-stroke depression (PSD) remains controversial. Lower testosterone levels caused by statins could potentially increase the risk of PSD. Low-dose statins could offer better benefits due to their lesser impact on testosterone levels. Repetitive transcranial magnetic stimulation (rTMS) has been shown to reduce PSD in the acute stage. The combination of low-dose statins and rTMS may provide a promising therapeutic option for patients with PSD.MethodsData were collected from ischemic stroke patients. Unsupervised machine learning methods were employed to explore the risk factor of PSD. Our prospective cohort study collected data from ischemic stroke patients over 3 years. The patients’ conditions determined the prescription of statins. The outcomes measured included the incidence of PSD, favorable functional outcome (FFO) at 6- and 12-months post-onset.ResultsA total of 545 patients were included in the study. The mean age was 60.99 ± 12.768 years, and 31.9% of the participants were female. The combination of low-dose statins and rTMS subgroup had the lowest incidence of PSD at both 6 and 12 months (p < 0.001). In multivariable logistic regression, the combination of low-dose statins and rTMS was inversely related to PSD at 6 months (OR = 0.370, p = 0.003) and 12 months (OR = 0.386, p = 0.004).ConclusionThe combination of statins and the rTMS group related the lower incidence of PSD in stroke patients. Combining low-dose statins and rTMS could reduce PSD and further improve the prognosis of ischemic stroke patients.